Analisis Ancaman Non-Tradisional di Perbatasan Laut Indonesia-Filipina Guna Mendukung Strategi Keamanan Laut Tentara Nasional Indonesia Angkatan Laut - Steifel Robert Mandey; Achmad Efendi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study analyzes non-traditional maritime threats at the Indonesia-Philippines sea border to support the Indonesian Navy’s (TNI AL) maritime security strategy. Utilizing SWOT analysis complemented by IFAS and EFAS matrices, the research identifies key internal strengths and weaknesses of TNI AL, as well as external opportunities and threats in the maritime border region. Findings reveal that while TNI AL possesses significant capabilities in experience, surveillance technology, and inter-agency cooperation, challenges remain in patrol vessel availability and technological limitations. External threats such as illegal fishing, smuggling, maritime terrorism, and piracy dominate the security landscape. The study recommends a Strengths-Threats (ST) strategy focusing on enhancing operational capacity, technological upgrades, increasing cooperation between maritime law enforcement agencies, and bilateral cooperation with the Philippines to effectively mitigate these threats. Implementation of these strategies is expected to strengthen maritime sovereignty and regional stability.